Reproduction and growth of the fish Lutjanus guttatus (Pisces: Lutjanidae) in the Gulf of Nicoya, Costa Rica - Soto Rojas, Rosa L.; Mejía Arana, Fernando; Palacios, J. A.; Hiramatsu, Kazuhito (Revista de Biología Tropical, 2009)
The fish Lutjanus guttatus is important in the fisheries of Golfo de Nicoya, Costa Rica where they are captured with varied gear mainly by the artisanal fleet. We measured specimens from the commercial catch of 2002-2006. Gonadal state was determined macroscopically and age with otoliths The total length-total weight relationship was y = 0.0236x2.8153 and total length-eviscerated weight y = 0.0216x2.8129. Simplified relationships were y = 0.0173x3 and y = 0.0162x3. There is year-round reproduction with peaks in March (dry season) and September (rainy season). Male-female sexual ratio was 1:1. The age-length key for the gulf shows availability until the 6 years of age. The von Bertalanffy growth curve is L (t) = 65,9 (1-e -0,13(t+2,66))